Price disclosure rules and consumer price comparison - Torben Stühmeier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Search frictions are classified as a main impediment to active competition in many markets. In some markets, such as in financial and retail gasoline markets, governments and consumer protection agencies call for a compulsory price reporting. Consumers should then more easily compare the firms' offers. We show that for a given level of price comparison, a mandatory price reporting indeed widely benefits consumers. The regulation, however, feeds back into firms' strategies, resulting in lower equilibrium levels of price comparison. This effect may dominate and the regulation may lead to higher expected market prices.
Keywords: D83; L13; L51; 330